Archivists, collectors, dealers, and replevin : case studies on private ownership of public documents - Dow, Elizabeth H. (The Scarecrow Press, Incorporated, 2012)
Today, governmental archivists and manuscript collectors-both private collectors and collecting repositories-are in conflict and competition for government documents that come out of private hands and onto the market. This book presents both sides of the issue and examines them dispassionately. It includes a historical review of institutional and state-sponsored collecting of documents, an evaluation of state and federal statutes on public documents in private hands, a careful look at the perspectives of the various parties involved in the conflict, and tales of theft and neg.